2010
DOI: 10.1137/090749013
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Imaging of Perfectly Conducting Cracks

Abstract: In this paper, we consider cracks with Dirichlet boundary conditions. We first derive an asymptotic expansion of the boundary perturbations that are due to the presence of a small crack. Based on this formula, we design a noniterative approach for locating a collection of small cracks. In order to do so, we construct a response matrix from the boundary measurements. The location and the length of the crack are estimated, respectively, from the projection onto the noise space and the first significant singular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
97
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 30 publications
(35 reference statements)
0
97
0
Order By: Relevance
“…Based on recent works in [4,6,19,20,24], it has been shown that subspace migration offers better results than the MUSIC and Kirchhoff migration. Specially, subspace migration can be applied to limited-view inverse scattering problems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on recent works in [4,6,19,20,24], it has been shown that subspace migration offers better results than the MUSIC and Kirchhoff migration. Specially, subspace migration can be applied to limited-view inverse scattering problems.…”
Section: Resultsmentioning
confidence: 99%
“…To find a good initial guess, alternative non-iterative reconstruction algorithms have been developed, such as the MUltiple SIgnal Classification (MUSIC)-type algorithm [5,23,25], linear sampling method [8,12], topological derivative strategy [3,6,18,21,22], linear-δ, vector and multipolarized approaches [29,30], and the multifrequency based algorithm such as Kirchhoff and subspace migrations [2,4,15,19,20,24]. Among them, although the multi-frequency based subspace migration has exhibited potential as a non-iterative imaging technique, a mathematical identification of its structure needs to be performed for its heuristical applications, which is the motivation behind.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method requires derivation of a complex Fréchet derivative, incurs large computational costs, and provides only a good initial guess regarding successful performance. Nevertheless, many practical experiments require starting with a good initial guess so alternative non-iterative imaging methods continue to be developed; e.g., the Multiple SIgnal Classification (MUSIC) algorithm [2], [3], linear sampling method [4], [5], and Kirchhoff migration [6], [7]. These appear to be fast and robust, and easily extend to the imaging of multiple cracks, but they still require a large number of incident fields with various directions and corresponding scattered field data.…”
Section: ⅰ Introductionmentioning
confidence: 99%
“…But their approach seems not clear how to be applied for different impedances. On the other hand, we would like to point out the recent developments in connection with our studied problem and suggested techniques, specially for small cracks, see, e.g., [1,2].…”
Section: Introductionmentioning
confidence: 99%